Assessing the adoption of regenerative agricultural practices in Eastern Africa - Ntawuhiganayo, Elisée Bahati; Nijman-Ross, Elke; Geme, Tom; Negesa, Doryn; Nahimana, Samuel (Frontiers in Sustainability, 2023)
Food security remains a challenge for Africa and regenerative agricultural practices can play an important role in building resilience while sustaining agricultural production and preserving diversity of ingredients and rich biodiversity. This study conducted surveys in eight regions in East Africa, four in Rwanda and four in Kenya, to understand how circular principles are applied in agriculture, potential drivers of the adoption of regenerative agriculture and its contribution to household food security. A binary logistic regression model was used to capture the influence of independent variables on the adoption of regenerative agricultural practices and determining factors of household food security. Farming households engage in less than four different practices, mainly in less labor-intensive practices such as crop rotation and intercropping. Household food security increased with an increased number of regenerative agricultural practices applied by the household and increased frequency of farm visits by extension agents. Regenerative agriculture practices, when applied in combinations, have the potential to increase household food security. This study recommends designing scaling-up pathways to accelerate the transition to regenerative agriculture and build a more resilient food system in East Africa.